Students critical thinking skills toward concepts differences in finding area of a plane region and definite integral - Susilo, Bambang Eko; Darhim, Darhim; Prabawanto, Sufyani (Unnes Journal of Mathematics Education, 2019)
This study aimed to describe students' critical thinking skills towards the concepts differences in finding the area of a plane region and definite integral. This study used an exploratory test survey method with test instruments. Data were taken from 40 students of the mathematics department at a university in Central Java. The results showed that students' critical thinking skills towards the concepts differences in finding the area of a plane region and definite integral were in the medium category. The students' critical thinking skills towards the concepts differences in finding area of a plane region and definite integral were medium (47.5%), with clarification by 57.5% (medium), assessment by 40.0% (medium), inference by 65.0% (medium), and strategies by 27.5% (low). These weaknesses are expected to be followed up by conducting learning that can show the linkages between the concepts and with various ways.